Konsep Ketenangan Jiwa Dalam Q.S. Al-Insyirah Studi Tafsir Al-Mishbah Karya M. Quraisy Shihab - Nurkhaeriyah Nurkhaeriyah; Toto Santi Aji (AL-MUFASSIR, 2021)
This article discusses M. Quraish Shihab's interpretation of the letter Al-Insyirah in the interpretation of al-Mishbah. This letter is known as one of the letters that provides guidance in dealing with the problems of human life in general, but actually the letter came down regarding the success of the Prophet Muhammad SAW in dealing with various kinds of difficulties and obstacles that came from unbelievers, then he got spaciousness and ease. , namely after he experienced victory in carrying out Allah's command to preach. This study is qualitative because the data source comes from the library. The research method that the author uses is descriptive analysis. The analysis used in this study is to use the analysis method of interpretation at-Tahlili